Peningkatan Literasi dan Numerasi Siswa SDN 221 Babakan Sentral Bandung dalam Program Kampus Mengajar - Rahman, Sidiq Aulia; Santoso, Dimas Arif; Saridaningsih, Firgi; Maulida, lian Assyra; Nurhasanah, Heti; Setia, Hevi Agnes (Lembaga Pengabdian kepada Masyarakat Universitas Langlangbuana, 2024)
The Kampus Mengajar (KM) program at the SDN 221 Babakan Sentral Bandung aims to enhance students' literacy and numeracy through innovative and interactive teaching approaches. This initiative is implemented using learning mentoring methods, literacy and numeracy enhancement programs, as well as curriculum adjustments and the utilization of school media and environment. The initial and final test results show significant improvements in literacy (44%-57%) and numeracy (44%-60%) among students. These findings indicate that innovative approaches, student engagement, and the use of educational play tools are effective in improving the quality of education. The implications of these results suggest the need for replicating similar programs in other schools facing similar challenges to continuously enhance students' literacy and numeracy.